2019
DOI: 10.1177/1071100719875220
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Ultrasound-Guided Gastrocnemius Injection With Botulinum Toxin for Chronic Plantar Fasciitis

Abstract: Background: The objective of this study was to determine whether the injection of botulinum toxin A (BTA) in the medial head of the gastrocnemius muscle could yield improvements in function and disability in patients with chronic plantar fasciitis with follow-up 12 months after treatment. Methods: Thirty-two patients with chronic plantar fasciitis were included in the study and randomly allocated to the BTA and placebo groups. The visual analog scale (VAS) and American Orthopaedic Foot & Ankle Society (AOF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 24 publications
1
22
0
Order By: Relevance
“…Thirty-two patients with chronic plantar fasciitis were randomized to the BTX-A and placebo groups, and 70 U of BTX-A was administered into the medial head of the gastrocnemius muscle under ultrasound guidance. The outcome of the present study showed that local injection of BTX-A into the gastrocnemius muscle had a positive effect on improving pain and foot function in the patients, and the effect lasted for over a year (Abbasian et al, 2019).…”
Section: Myofascial Painsupporting
confidence: 50%
“…Thirty-two patients with chronic plantar fasciitis were randomized to the BTX-A and placebo groups, and 70 U of BTX-A was administered into the medial head of the gastrocnemius muscle under ultrasound guidance. The outcome of the present study showed that local injection of BTX-A into the gastrocnemius muscle had a positive effect on improving pain and foot function in the patients, and the effect lasted for over a year (Abbasian et al, 2019).…”
Section: Myofascial Painsupporting
confidence: 50%
“…Ninety-four randomized controlled trials (5397 participants) assessed pain in the short term as an outcome. Of these, 51 randomized controlled trials (2937 participants) compared 14 different therapeutic interventions to the control group in the short term: acupuncture ( n = 69 19,20,23 ); botulinum toxin ( n = 161 27,31,33,34 ); corticosteroid injection ( n = 244 107,108,168,186 ) ; dry needling ( n = 215 39,41,42 ); extracorporeal shock wave therapy ( n = 863 54,55,65,71,72,75,78,81,84,166 ); low-dye taping ( n = 213 106,115,119,231 ); low-level laser therapy ( n = 231 122,125,133,129,132 ); micronized dehydrated human amnion/chorion membrane injection ( n = 175 92,93 ), myofascial releases ( n = 101 212,214,215,222 ); orthosis ( n = 259 141,148,160,162 ); platelet-rich plasma ( n = 110 181,186 ); radiofrequency ( n = 87 236,237 ); stretching ( n = 112 230,231 ); and therapeutic ultrasound ( n = 97 250,251 ). A summary of the meta-analysis performed to compare interventions versus controls is shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, botulinum toxin A injection into the medial gastrocnemius resulted in decreased VAS, increased AOFAS scores, and improved dorsiflexion when compared with a saline injection alone. 1 Athletic performance did not decrease.…”
Section: Indications Plantar Fasciitismentioning
confidence: 90%